KOMUNIKASI INTERPERSONAL GURU DAN SISWA DALAM PEMANFAATAN MICROSOFT TEAMS PADA BLENDED LEARNING - Nurfatma Kumalahayati; Kiayati Yusriyah (WACANA: Jurnal Ilmiah Ilmu Komunikasi, 2022)
Good interpersonal communication between teachers and students in the learning process is very necessary for the smooth running of effective learning, after the implementation of restrictions in the Covid19 era made schools implement blended learning so that the use of Microsoft Teams was used by schools as LMS to help teachers and students. students in the learning process. The purpose of this study is to determine the interpersonal communication of teachers and students in the use of Microsoft Teams, the supporting factors and barriers to interpersonal communication and how effective interpersonal communication is between teachers and students in the blended learning process of Senior High Schools in Bekasi City. The research method used is descriptive qualitative with a case study approach. Data was collected through observation, documentation, and interviews. The results show that interpersonal communication between teachers and students has been running quite effectively with the use of Microsoft Teams as a learning medium that helps teachers and students to be able to connect to online learning in the Covid19 pandemic era. There is openness, empathy, supportive attitude, positive attitude, and equality shown by teachers and students so that there is effectiveness of interpersonal communication.